Auditory information processing for sound perception and vocalization in case of tritone paradox - HAFKE, Honorata (Archives of Acoustics, 2008)
The aim of this paper is to answer the question whether "perception-action" dissociation, which is well-documented in vision, may also be found in auditory information processing in case of the tritone paradox. Two experiments were conducted. Sounds with the ambiguous pitch were utilized. They were precisely classified as a note (eg. C, C#, F#), but equivocal as to octave. In the experiment A, participants were asked to aurally estimate pitch shifts of sounds divided by the interval of tritone. In the experiment B, participants were asked to reproduce a pair of tritones, by singing the vowel "a". Results of the two experiments were compared, in order to determine if task specification - perceptive (experiment A) or motor (experiment B) - can cause dissimilar results.